Analysis and Comparison of Natural Shear and Induced Tensile Fractures for Caprock Leakage Assessment - Sahyuo Achuo Dze; Tomos Phillips; Reza Najafi-Silab; Sarah Perez; Tom Bultreys; Vladimir Novak; Christian M. Schlepütz; Veerle Cnudde; Florian Doster; Kamaljit Singh; Kevin Bisdom; Andreas Busch (Transport in Porous Media, 2026)
The comparison between laboratory-induced and subsurface fractures, and their corresponding flow is still unclear. Here, we examine three natural shear fractures and two induced tensile fractures from the same low-permeability lithology. Using high-resolution synchrotron imaging, we extracted three-dimensional fracture void geometries to analyse aperture distributions, surface roughness, and spatial correlation patterns. We then compared measured fracture transmissivities against theoretical predictions from parallel-plate models (cubic law) and direct numerical simulations (DNS) of flow to evaluate consistency and uncertainties. We find that despite differences in heterogeneity, induced tensile and natural shear fractures can generally yield similar flow in caprocks. Our comparisons further indicate that the choice of flow estimation method can introduce more uncertainty than the fracture opening mode.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

P22-32 Knowledge Infrastructure supporting image-based characterisation of 2D graphene materials - P.P. Ankli; A.A. Abdelwahab; A. Logachov; R. Bugiel; D. Drobne; S. Novak; E. Kranjc; S. Saje; F. Pellegrino; E. Alladio; F. Sordello; E. Corrao; et al. (Toxicology Letters, 2025)

ADMET parameters of tacrine and its metabolites confirm unsuitability of Sus scrofa f. domestica model to study tacrine-associated hepatotoxicity - M. Novak; J. Bureš; V. Radochová; J. Pejchal; L. Prchal; O. Soukup (Chemico-Biological Interactions, 2025)

Understanding Wave Attenuation Across Marshes: Insights from Numerical Modeling - Madeline R. Foster-Martinez; Ioannis Y. Georgiou; Duncan M. FitzGerald; Zoe J. Hughes; Alyssa Novak; Md Mohiuddin Sakib (Journal of Marine Science and Engineering, 2025)
Marsh vegetation dampens wave energy, providing protection to coastal communities from storms. A new modeling framework was applied to study wave height evolution over the saltmarsh bordering Newbury, MA. A regional Delft3D hydrodynamic model generated wind driver waves in the open water portions of the study area, which were then one-way coupled with an analytical model, the Marsh Transect Wave Attenuation (MTWA) model, which tracked wave evolution along select transects throughout the marsh. Field observations of vegetation and wave height evolution were used to calibrate MTWA. Seven scenarios were run covering a range of possible future management and environmental conditions, in addition to projected sea level rise. Results underscore the importance of vegetation and elevation to wave attenuation.

Hazard characterization of the mycotoxins enniatins and beauvericin to identify data gaps and improve risk assessment for human health - Anne-Cathrin Behr; Christiane Kruse Fæste; Amaya Azqueta; Ana M. Tavares; Anastasia Spyropoulou; Anita Solhaug; Ann-Karin Olsen; Ariane Vettorazzi; Birgit Mertens; Bojana Zegura; Camille Streel; Dieynaba Ndiaye; et al. (Archives of Toxicology, 2025)
Enniatins (ENNs) and beauvericin (BEA) are cyclic hexadepsipeptide fungal metabolites which have demonstrated antibiotic, antimycotic, and insecticidal activities. The substantial toxic potentials of these mycotoxins are associated with their ionophoric molecular properties and relatively high lipophilicities. ENNs occur extensively in grain and grain-derived products and are considered a food safety issue by the European Food Safety Authority (EFSA). The tolerable daily intake and maximum levels for ENNs in humans and animals remain unestablished due to key toxicological and toxicokinetic data gaps, preventing full risk assessment. Aiming to find critical data gaps impeding hazard characterization and risk evaluation, this review presents a comprehensive summary of the existing information from in vitro and in vivo studies on toxicokinetic characteristics and cytotoxic, genotoxic, immunotoxic, endocrine, reproductive and developmental effects of the most prevalent ENN analogues (ENN A, A1, B, B1) and BEA. The missing information identified showed that additional studies on ENNs and BEA have to be performed before sufficient data for an in-depth hazard characterisation of these mycotoxins become available.

Early insights into the seasonal and spatial distribution of white sharks (Carcharodon carcharias) along the Maine coastline - Matthew M. Davis; Megan V. Winton; John A. Mohan; Joseph D. Iafrate; James A. Sulikowski; Blaise P. Jenner; Ashleigh J. Novak; Victoria Migneco; Tobey H. Curtis; Chip Michalove; Gregory B. Skomal (Frontiers in Marine Science, 2025)
While significant progress has been made to characterize life history patterns, movement ecology, and regional estimates of abundance of white sharks ( Carcharodon carcharias ) in the Western North Atlantic (WNA), patterns of spatial distribution remain relatively unknown in the northern Gulf of Maine. In this study, we utilize data collected from multiple acoustic telemetry projects from 2012-2023 to assess the spatiotemporal distribution of white sharks along sections of the Maine coastline and regional offshore waters. Acoustic receivers were deployed each year from 2012-2019 (mean number of receivers ± SD: 11 ± 4), and effort increased following the first-ever white shark related fatality in Maine in 2020 (2020-2023: 40 ± 15). In total, 107 white sharks tagged by researchers in the WNA were detected, with the majority (n = 90) detected in shallow (<50 m depth) waters post-2019. Reflective of the tagged population at-large, total length of individuals ranged from 2.1 to 4.9 m, with most individuals estimated to be in the juvenile or subadult life stages. White sharks were detected between the months of May-December, with peaks between July and September, and were observed in close proximity to several of Maine’s western beaches and islands/outcroppings, with higher numbers observed at several sites in eastern Casco Bay. Although the overall quantity of detections was relatively low when compared to white shark aggregation sites in other regions, this study provides baseline information on the presence of this species in the northern Gulf of Maine. While future research should include expanded receiver coverage in eastern Maine and the use of additional tagging technologies, this study contributes early insights for informing marine spatial planning, fisheries management, and conservation strategies for white sharks in the region.

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Janus nanocellulose membrane by nitrogen plasma: Hydrophilicity to hydrophobicity selective switch - Ana Oberlintner; Vasyl Shvalya; Neelakandan M. Santhosh; Martin Košiček; Ivan Jerman; Matej Huš; Uroš Cvelbar; Uroš Novak; Blaž Likozar (Carbohydrate Polymers, 2024)

Emerging Scientific Approaches for Identifying Ecologically Adverse Effects of Air Pollution - S. Douglas Kaylor; Rebecca M. Dalton; Tara Greaver; Jeffrey D. Herrick; Emma Leath; Kristopher Novak; Caroline E. Ridley (Environmental Management, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Author Correction: Hazard characterization of Alternaria toxins to identify data gaps and improve risk assessment for human health - Henriqueta Louro; Ariane Vettorazzi; Adela López de Cerain; Anastasia Spyropoulou; Anita Solhaug; Anne Straumfors; Anne-Cathrin Behr; Birgit Mertens; Bojana Žegura; Christiane Kruse Fæste; Dieynaba Ndiaye; Eliana Spilioti; et al. (Archives of Toxicology, 2024)

P19-45 Data management for image-based characterisation of 2D nano-materials - P.P. Ankli; A. Ali; S. Hodzic; A. Logachov; K. Maciejczuk; A. Milochiv; S. Hardy; B. Hardy; S. Novak; E. Kranjc; V. Kononenko; S. Saje; et al. (Toxicology Letters, 2024)

P02-11 Enhancing genotoxicity assessment: advanced 3D cell models for chemical testing - I. Durmišević; A. Haverić; M. Štampar; S. Žabkar; M. Hadžić Omanović; T. Ćetković Pećar; A. Štern; K. Kološa; M. Novak; K. Fras; S. Haverić; B. Žegura (Toxicology Letters, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Influence of Local Aperture Heterogeneity on Invading Fluid Connectivity During Rough Fracture Drainage - Tomos Phillips; Tom Bultreys; Jeroen Van Stappen; Kamaljit Singh; Sahyuo Achuo Dze; Stefanie Van Offenwert; Ben Callow; Mostafa Borji; Erik Clemens Boersheim; Vladimir Novak; Christian M. Schlepütz; Veerle Cnudde; et al. (Transport in Porous Media, 2024)
Determining the (in)efficiency of wetting phase displacement by an invading non-wetting phase (drainage) in a single fracture is key to modelling upscaled properties such as relative permeability and capillary pressure. These constitutive relationships are fundamental to quantifying the contribution, or lack thereof, of conductive fracture systems to long-term leakage rates. Single-fracture-scale modelling and experimental studies have investigated this process, however, a lack of visualization of drainage in a truly representative sample at sufficient spatial and temporal resolution limits their predictive insights. Here, we used fast synchrotron X-ray tomography to image drainage in a natural geological fracture by capturing consecutive 2.75 μm voxel images with a 1 s scan time. Drainage was conducted under capillary-dominated conditions, where percolation-type patterns are expected. We observe this continuously connected invasion (capillary fingering) only to be valid in local regions with relative roughness, λ b ≤ 0.56. Fractal dimension analysis of these invasion patterns strongly aligns with capillary fingering patterns previously reported in low λ b fractures and porous media. Connected invasion is prevented from being the dominant invasion mechanism globally due to high aperture heterogeneity, where we observe disconnected invasion (snap-off, fragmented clusters) to be pervasive in local regions where λ b ≥ 0.67. Our results indicate that relative roughness has significant control on flow as it influences fluid conductivity and thus provides an important metric to predict invasion dynamics during slow drainage.

Microplastic abundance and accumulation patterns in eelgrass (Zostera marina L.) meadows throughout coastal Massachusetts, USA - Alyssa B. Novak; Cecelia M. Gerstenbacher; Karina Scavo Lord; Randi D. Rotjan (Environmental Monitoring and Assessment, 2024)

Hazard characterization of Alternaria toxins to identify data gaps and improve risk assessment for human health - Henriqueta Louro; Ariane Vettorazzi; Adela López de Cerain; Anastasia Spyropoulou; Anita Solhaug; Anne Straumfors; Anne-Cathrin Behr; Birgit Mertens; Bojana Žegura; Christiane Kruse Fæste; Dieynaba Ndiaye; Eliana Spilioti; et al. (Archives of Toxicology, 2024)
Fungi of the genus Alternaria are ubiquitous plant pathogens and saprophytes which are able to grow under varying temperature and moisture conditions as well as on a large range of substrates. A spectrum of structurally diverse secondary metabolites with toxic potential has been identified, but occurrence and relative proportion of the different metabolites in complex mixtures depend on strain, substrate, and growth conditions. This review compiles the available knowledge on hazard identification and characterization of Alternaria toxins. Alternariol (AOH), its monomethylether AME and the perylene quinones altertoxin I (ATX-I), ATX-II, ATX-III, alterperylenol (ALP), and stemphyltoxin III (STTX-III) showed in vitro genotoxic and mutagenic properties. Of all identified Alternaria toxins, the epoxide-bearing analogs ATX-II, ATX-III, and STTX-III show the highest cytotoxic, genotoxic, and mutagenic potential in vitro . Under hormone-sensitive conditions, AOH and AME act as moderate xenoestrogens, but in silico modeling predicts further Alternaria toxins as potential estrogenic factors. Recent studies indicate also an immunosuppressive role of AOH and ATX-II; however, no data are available for the majority of Alternaria toxins. Overall, hazard characterization of Alternaria toxins focused, so far, primarily on the commercially available dibenzo-α-pyrones AOH and AME and tenuazonic acid (TeA). Limited data sets are available for altersetin (ALS), altenuene (ALT), and tentoxin (TEN). The occurrence and toxicological relevance of perylene quinone-based Alternaria toxins still remain to be fully elucidated. We identified data gaps on hazard identification and characterization crucial to improve risk assessment of Alternaria mycotoxins for consumers and occupationally exposed workers.

Instream constructed wetland capacity at controlling phosphorus outflow under a long‐term nutrient loading scenario: approach using SWAT model - Clement D. Sohoulande Djebou; Ariel A. Szogi; Jeff M. Novak; Kenneth C. Stone; Jerry H. Martin; Don Watts (Modeling Earth Systems and Environment, 2023)

P26-14: Assessment of tyrosine kinase inhibitors cytotoxic and genotoxic effects in non-target zebrafish liver (ZFL) cells in vitro - K. Kološa; M. Novak; M. Štampar; B. Žegura; M. Filipič (Toxicology Letters, 2023)

P17-12: Study quality criteria for nanoplastics: a case study on polystyrene nanoplastics and the aquatic invertebrate Daphnia spp. - D. Kuehnel; M. Heinlaan; S. Novak; D. Drobne; A.J. Kokalj (Toxicology Letters, 2023)

Mixing behavior of dissolved organic matter at the Yukon and Kolyma land ocean interface - Anne M. Kellerman; Peter J. Hernes; Amy M. McKenna; J. Blake Clark; Augusta Edmund; Brice Grunert; Paul J. Mann; Antonio Mannino; Michael Novak; Aron Stubbins; Maria Tzortziou; Nikita Zimov; et al. (Marine Chemistry, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Scavenger receptor BI attenuates oxidized phospholipid-induced pulmonary inflammation - Katelyn Dunigan-Russell; Michael J. Yaeger; Myles X. Hodge; Brita Kilburg-Basnyat; Sky W. Reece; Anastasiya Birukova; Marissa A. Guttenberg; Caymen Novak; Sangwoon Chung; Brandie Michelle Ehrmann; E. Diane Wallace; Debra Tokarz; et al. (Toxicology and Applied Pharmacology, 2023)

Synergistic effects of agonists and two-pore-domain potassium channels on secretory responses of human pancreatic duct cells Capan-1 - Christiane E. Sørensen; Anna Trauzold; Nynne M. Christensen; Doaa Tawfik; Monika Szczepanowski; Ivana Novak (Pflügers Archiv - European Journal of Physiology, 2023)
Mechanisms of synergistic agonist stimulation and modulation of the electrochemical driving force for anion secretion are still not fully explored in human pancreatic duct epithelial cells. The first objective of this study was therefore to test whether combined agonist stimulation augments anion transport responses in the Capan-1 monolayer model of human pancreatic duct epithelium. The second objective was to test the influence of H + ,K + -ATPase inhibition on anion transport in Capan-1 monolayers. The third objective was to analyze the expression and function of K + channels in Capan-1, which could support anion secretion and cooperate with H + ,K + -ATPases in pH and potassium homeostasis. The human pancreatic adenocarcinoma cell line Capan-1 was cultured conventionally or as polarized monolayers that were analyzed by Ussing chamber electrophysiological recordings. Single-cell intracellular calcium was assayed with Fura-2. mRNA isolated from Capan-1 was analyzed by use of the nCounter assay or RT-PCR. Protein expression was assessed by immunofluorescence and western blot analyses. Combined stimulation with different physiological agonists enhanced anion transport responses compared to single agonist stimulation. The responsiveness of Capan-1 cells to histamine was also revealed in these experiments. The H + ,K + -ATPase inhibitor omeprazole reduced carbachol- and riluzole-induced anion transport responses. Transcript analyses revealed abundant TASK-2, TWIK-1, TWIK-2, TASK-5, K Ca3.1 , and KCNQ1 mRNA expression. KCNE1 mRNA and TREK-1, TREK-2, TASK-2, and KCNQ1 protein expression were also shown. This study shows that the Capan-1 model recapitulates key physiological aspects of a bicarbonate-secreting epithelium and constitutes a valuable model for functional studies on human pancreatic duct epithelium.

Environmental and bioclimatic factors influencing yeasts and molds distribution along European shores - M. Cogliati; S. Arikan-Akdagli; A. Barac; A.C. Bostanaru; S. Brito; N. Çerikçioğlu; M.A. Efstratiou; Ç. Ergin; M.C. Esposto; M. Frenkel; J.P. Gangneux; A. Gitto; et al. (Science of The Total Environment, 2023)

Ozone impairs endogenous compensatory responses in allergic asthma - Kevin Ho; David Weimar; Gina Torres-Matias; Hyunwook Lee; Saaleha Shamsi; Emily Shalosky; Michael Yaeger; Hannah Hartzler-Lovins; Katelyn Dunigan-Russell; Daria Jelic; Caymen M. Novak; Kymberly M. Gowdy; et al. (Toxicology and Applied Pharmacology, 2023)

Interdisciplinary design of a fish ramp using migration routes analysis - Gorazd Novak; Polona Pengal; Ana T. Silva; José M. Domínguez; Angelo Tafuni; Matjaž Četina; Dušan Žagar (Ecological Modelling, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Arctic biogeochemical and optical properties of dissolved organic matter across river to sea gradients - Michael G. Novak; Antonio Mannino; J. Blake Clark; Peter Hernes; Maria Tzortziou; Robert G. M. Spencer; Anne M. Kellerman; Brice Grunert (Frontiers in Marine Science, 2022)
Arctic landscapes are warming and becoming wetter due to changes in precipitation and the timing of snowmelt which consequently alters seasonal runoff and river discharge patterns. These changes in hydrology lead to increased mobilization and transport of terrestrial dissolved organic matter (DOM) to Arctic coastal seas where significant impacts on biogeochemical cycling can occur. Here, we present measurements of dissolved organic carbon (DOC) and chromophoric DOM (CDOM) in the Yukon River-to-Bering Sea system and two river plumes on the Alaska North Slope which flow into the Beaufort Sea. Our sampling characterized optical and biogeochemical properties of DOM during high and low river discharge periods for the Yukon River-Bering Sea system. The average DOC concentration at the multiple Yukon River mouths ranged from a high of 10.36 mg C L -1 during the ascending limb of the 2019 freshet (late May), 6.4 mg C L -1 during the descending limb of the 2019 freshet (late June), and a low of 3.86 mg C L -1 during low river discharge in August 2018. CDOM absorption coefficient at 412 nm ( a CDOM (412)) averaged 8.23 m -1 , 5.07 m -1 , and 1.9 m -1 , respectively. Several approaches to model DOC concentration based on its relationship with CDOM properties demonstrated cross-system seasonal and spatial robustness for these Arctic coastal systems despite spanning an order of magnitude decrease in DOC concentration from the lower Yukon River to the Northern Bering Sea as well as the North Slope systems. “Snapshot” fluxes of DOC and CDOM across the Yukon River Delta to Norton Sound were calculated from our measurements and modeled water fluxes forced with upstream USGS river gauge data. Our findings suggest that during high river flow, DOM reaches the delta largely unaltered by inputs or physical and biogeochemical processing and that the transformations of Yukon River DOM largely occur in the plume. However, during low summer discharge, multiple processes including local precipitation events, microbial decomposition, photochemistry, and likely others can alter the DOM properties within the lower Yukon River and Delta prior to flowing into Norton Sound.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Following the Sand Grains - Duncan M. FitzGerald; Zoe J. Hughes; Alice Staro; Christopher J. Hein; Md Mohiuddin Sakib; Ioannis Y. Georgiou; Alyssa Novak (Journal of Marine Science and Engineering, 2022)
When longshore transport systems encounter tidal inlets, complex mechanisms are involved in bypassing sand to downdrift barriers. Here, this process is examined at Plum Island Sound and Essex Inlets, Massachusetts, USA. One major finding from this study is that sand is transferred along the coast—especially at tidal inlets—by parcels, in discrete steps, and over decadal-scale periods. The southerly orientation of the main-ebb channel at Plum Island Sound, coupled with the landward migration of bars from the ebb delta to the central portion of the downdrift Castle Neck barrier island, have formed a beach protuberance. During the constructional phase, sand is sequestered at the protuberance and the spit-end of the barrier becomes sediment starved, leading to shoreline retreat and a broadening of the spit platform at the mouth to Essex Bay (downdrift side of Castle Neck). Storm-induced sand transport from erosion of the spit and across the spit platform is washed into Essex Bay, filling channels and enlarging flood deltas. This study illustrates the pathways and processes of sand transfer along the shoreline of a barrier-island/tidal-inlet system and provides an important example of the processes that future hydrodynamic and sediment-transport modeling should strive to replicate.

Anti-neoplastic pharmacophore benzophenone-1 coumarin (BP-1C) targets JAK2 to induce apoptosis in lung cancer - Ankith Sherapura; Vikas H. Malojirao; Prabhu Thirusangu; B. S. Sharath; Shivananda Kandagalla; V. Vigneshwaran; Jurica Novak; Lakshmi Ranganatha; Y. L. Ramachandra; Shrinath M. Baliga; Shaukath Ara Khanum; B. T. Prabhakar (Apoptosis, 2022)

A Novel Framework to Predict Relative Habitat Selection in Aquatic Systems: Applying Machine Learning and Resource Selection Functions to Acoustic Telemetry Data From Multiple Shark Species - Lucas P. Griffin; Grace A. Casselberry; Kristen M. Hart; Adrian Jordaan; Sarah L. Becker; Ashleigh J. Novak; Bryan M. DeAngelis; Clayton G. Pollock; Ian Lundgren; Zandy Hillis-Starr; Andy J. Danylchuk; Gregory B. Skomal (Frontiers in Marine Science, 2021)
Resource selection functions (RSFs) have been widely applied to animal tracking data to examine relative habitat selection and to help guide management and conservation strategies. While readily used in terrestrial ecology, RSFs have yet to be extensively used within marine systems. As acoustic telemetry continues to be a pervasive approach within marine environments, incorporation of RSFs can provide new insights to help prioritize habitat protection and restoration to meet conservation goals. To overcome statistical hurdles and achieve high prediction accuracy, machine learning algorithms could be paired with RSFs to predict relative habitat selection for a species within and even outside the monitoring range of acoustic receiver arrays, making this a valuable tool for marine ecologists and resource managers. Here, we apply RSFs using machine learning to an acoustic telemetry dataset of four shark species to explore and predict species-specific habitat selection within a marine protected area. In addition, we also apply this RSF-machine learning approach to investigate predator-prey relationships by comparing and averaging tiger shark relative selection values with the relative selection values derived for eight potential prey-species. We provide methodological considerations along with a framework and flexible approach to apply RSFs with machine learning algorithms to acoustic telemetry data and suggest marine ecologists and resource managers consider adopting such tools to help guide both conservation and management strategies.

Behaviour of Cr in runoff from two catchments underlain by felsic bedrock - A. V. Andronikov; M. Novak; P. Kram; O. Sebek; I. E. Andronikova; N. A. Efremenko; G. S. Borodulina; D. A. Subetto; M. Stepanova; E. Antalova; M. A. Levichev; M. V. Zobkova; et al. (Hydrological Sciences Journal, 2020)

Correction to: Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)

Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)
Increasing the protection of coastal vegetated ecosystems has been suggested as one strategy to compensate for increasing carbon dioxide (CO 2 ) in the atmosphere as the capacity of these habitats to sequester and store carbon exceeds that of terrestrial habitats. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems and have an exceptional ability to sequester and store large quantities of carbon in biomass and, particularly, in sediments. However, carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows are highly variable both spatially and temporally, making it difficult to extrapolate this strategy to areas where information is lacking. In this study, C org stocks and C org accumulation were determined at 11 eelgrass meadows across New England, representing a range of eutrophication and exposure conditions. In addition, the environmental factors and structural characteristics of meadows related to variation in C org stocks were identified. The objectives were accomplished by assessing stable isotopes of δ 13 C and δ 15 N as well as %C and %N in plant tissues and sediments, measuring grain size and 210 Pb of sediment cores, and through assessing site exposure. Variability in C org stocks in seagrass meadows is well predicted using commonly measured environmental variables such as grain size distribution. This study allows incorporation of data and insights for the northwest Atlantic, where few studies on carbon sequestration by seagrasses have been conducted.

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

The Effect of Inorganic Salt on Disintegration of Tablets with High Loading of Amorphous Solid Dispersion Containing Copovidone - Hanmi Xi; Jie Ren; Julie M. Novak; Eric Kemp; Gregory Johnson; Gerard Klinzing; Mary Ann Johnson; Wei Xu (Pharmaceutical Research, 2020)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

One river, two streams: chemical and chromium isotopic features of the Neglinka River (Karelia, northwest Russia) - A. V. Andronikov; M. Novak; G. S. Borodulina; N. A. Efremenko; I. E. Andronikova; G. L. Chesalina; M. A. Levichev; D. A. Subetto; O. Sebek; M. V. Zobkova (Hydrological Sciences Journal, 2019)

The development and use of a spatially explicit model for river otters to evaluate environmental hazards: a case study on the Department of Energy’s Savannah River Site - Emily B. McCallen; Karen F. Gaines; James M. Novak; Leslie E. Ruyle; Warren L. Stephens; A. Lawrence Bryan; Susan A. Blas; Thomas L. Serfass (Environmental Monitoring and Assessment, 2018)

What drives interaction strengths in complex food webs? A test with feeding rates of a generalist stream predator - Daniel L. Preston; Jeremy S. Henderson; Landon P. Falke; Leah M. Segui; Tamara J. Layden; Mark Novak (Ecology, 2018)
Describing the mechanisms that drive variation in species interaction strengths is central to understanding, predicting, and managing community dynamics. Multiple factors have been linked to trophic interaction strength variation, including species densities, species traits, and abiotic factors. Yet most empirical tests of the relative roles of multiple mechanisms that drive variation have been limited to simplified experiments that may diverge from the dynamics of natural food webs. Here, we used a field‐based observational approach to quantify the roles of prey density, predator density, predator‐prey body‐mass ratios, prey identity, and abiotic factors in driving variation in feeding rates of reticulate sculpin ( Cottus perplexus ). We combined data on over 6,000 predator‐prey observations with prey identification time functions to estimate 289 prey‐specific feeding rates at nine stream sites in Oregon. Feeding rates on 57 prey types showed an approximately log‐normal distribution, with few strong and many weak interactions. Model selection indicated that prey density, followed by prey identity, were the two most important predictors of prey‐specific sculpin feeding rates. Feeding rates showed a positive relationship with prey taxon densities that was inconsistent with predator saturation predicted by current functional response models. Feeding rates also exhibited four orders‐of‐magnitude in variation across prey taxonomic orders, with the lowest feeding rates observed on prey with significant anti‐predator defenses. Body‐mass ratios were the third most important predictor variable, showing a hump‐shaped relationship with the highest feeding rates at intermediate ratios. Sculpin density was negatively correlated with feeding rates, consistent with the presence of intraspecific predator interference. Our results highlight how multiple co‐occurring drivers shape trophic interactions in nature and underscore ways in which simplified experiments or reliance on scaling laws alone may lead to biased inferences about the structure and dynamics of species‐rich food webs.

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

KCa3.1 (IK) modulates pancreatic cancer cell migration, invasion and proliferation: anomalous effects on TRAM-34 - B. Bonito; D. R. P Sauter; A. Schwab; M. B. A Djamgoz; I. Novak (Pflügers Archiv - European Journal of Physiology, 2016)

Microbial community structure of a freshwater system receiving wastewater effluent - Matthew D. Hladilek; Karen F. Gaines; James M. Novak; David A. Collard; Daniel B. Johnson; Thomas Canam (Environmental Monitoring and Assessment, 2016)

Designing advanced biochar products for maximizing greenhouse gas mitigation potential - Sanchita Mandal; Binoy Sarkar; Nanthi Bolan; Jeff Novak; Yong Sik Ok; Lukas Van Zwieten; Bhupinder Pal Singh; M. B. Kirkham; Girish Choppala; Kurt Spokas; Ravi Naidu (Critical Reviews in Environmental Science and Technology, 2016)

The adenosine A2B receptor is involved in anion secretion in human pancreatic duct Capan-1 epithelial cells - M. Hayashi; A. Inagaki; I. Novak; H. Matsuda (Pflügers Archiv - European Journal of Physiology, 2016)

Soil Health, Crop Productivity, Microbial Transport, and Mine Spoil Response to Biochars - J. M. Novak; J. A. Ippolito; R. D. Lentz; K. A. Spokas; C. H. Bolster; K. Sistani; K. M. Trippe; C. L. Phillips; M. G. Johnson (BioEnergy Research, 2016)

17β-Estradiol influent and effluent concentrations in wastewater: demographic influences and the risk to environmental health - K. T. Heffron; K. F. Gaines; J. M. Novak; T. Canam; D. A. Collard (Environmental Monitoring and Assessment, 2016)

ATP release, generation and hydrolysis in exocrine pancreatic duct cells - J. M. Kowal; G. G. Yegutkin; I. Novak (Purinergic Signalling, 2015)

Temporal variation in benthic primary production in streams of the Australian wet–dry tropics - Erica A. Garcia; Neil E. Pettit; Danielle M. Warfe; Peter M. Davies; Peter M. Kyne; Peter Novak; Michael M. Douglas (Hydrobiologia, 2015)

Timescales alter the inferred strength and temporal consistency of intraspecific diet specialization - Mark Novak; M. Tim Tinker (Oecologia, 2015)

Spatio-temporal distribution of Grapevine fanleaf virus (GFLV) in grapevine - Anastazija Jež Krebelj; Urška Čepin; Maja Ravnikar; M Pompe-Novak (European Journal of Plant Pathology, 2015)

Atrazine and glyphosate dynamics in a lotic ecosystem: the common snapping turtle as a sentinel species - Derrick L. Douros; Karen F. Gaines; James M. Novak (Environmental Monitoring and Assessment, 2015)

Dual functions of NME1 in suppression of cell motility and enhancement of genomic stability in melanoma - David M. Kaetzel; Mary K. Leonard; Gemma S. Cook; Marian Novak; Stuart G. Jarrett; Xiuwei Yang; Alexey M. Belkin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Plant Macro- and Micronutrient Dynamics in a Biochar-Amended Wetland Muck - J. M. Novak; G. C. Sigua; K. A. Spokas; W. J. Busscher; K. B. Cantrell; D. W. Watts; B. Glaz; P. G. Hunt (Water, Air, & Soil Pollution, 2015)

Comparative gene expression profiling reveals key changes in expression levels of cephalosporin C biosynthesis and transport genes between low and high-producing strains of Acremonium chrysogenum - M. V. Dumina; A. A. Zhgun; M. I. Novak; A. G. Domratcheva; D. V. Petukhov; V. V. Dzhavakhiya; M. A. Eldarov; Iu. E. Bartoshevitch (World Journal of Microbiology and Biotechnology, 2014)

Role of vesicular nucleotide transporter VNUT (SLC17A9) in release of ATP from AR42J cells and mouse pancreatic acinar cells - K. A. Haanes; J. M. Kowal; G. Arpino; S. C. Lange; Y. Moriyama; P. A. Pedersen; I. Novak (Purinergic Signalling, 2014)

Phenolic Acid Sorption to Biochars from Mixtures of Feedstock Materials - K. E. Hall; M. J. Calderon; K. A. Spokas; L. Cox; W. C. Koskinen; J. Novak; K. Cantrell (Water, Air, & Soil Pollution, 2014)

UTP-induced ATP release is a fine-tuned signalling pathway in osteocytes - Tina M. Kringelbach; Derya Aslan; Ivana Novak; Peter Schwarz; Niklas R. Jørgensen (Purinergic Signalling, 2014)

Influence of Corn Residue Harvest Management on Grain, Stover, and Energy Yields - Keri B. Cantrell; Jeffrey M. Novak; James R. Frederick; Douglas L. Karlen; Donald W. Watts (BioEnergy Research, 2014)

Distribution of Structural Carbohydrates in Corn Plants Across the Southeastern USA - Spyridon Mourtzinis; Keri B. Cantrell; Francisco J. Arriaga; Kipling S. Balkcom; Jeff M. Novak; James R. Frederick; Douglas L. Karlen (BioEnergy Research, 2014)

Soil Microbial Community Response to Corn Stover Harvesting Under Rain-Fed, No-Till Conditions at Multiple US Locations - R. Michael Lehman; Thomas F. Ducey; Virginia L. Jin; Veronica Acosta-Martinez; Carla M. Ahlschwede; Elizabeth S. Jeske; Rhae A. Drijber; Keri B. Cantrell; James R. Frederick; Darci M. Fink; Shannon L. Osborne; Jeff M. Novak; et al. (BioEnergy Research, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Crop Residue Mass Needed to Maintain Soil Organic Carbon Levels: Can It Be Determined? - Jane M. F. Johnson; Jeff M. Novak; Gary E. Varvel; Diane E. Stott; Shannon L. Osborne; Douglas L. Karlen; John A. Lamb; John Baker; Paul R. Adler (BioEnergy Research, 2014)

Toxicodynamic modeling of 137Cs to estimate white-tailed deer background levels for the Department of Energy's Savannah River Site - Karen F. Gaines; James M. Novak; Christopher W. Bobryk; Susan A. Blas (Environmental Monitoring and Assessment, 2014)

Designing relevant biochars as soil amendments using lignocellulosic-based and manure-based feedstocks - Jeffrey M. Novak; Keri B. Cantrell; Donald W. Watts; Warren J. Busscher; Mark G. Johnson (Journal of Soils and Sediments, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Trophic dynamics of U, Ni, Hg and other contaminants of potential concern on the Department of Energy’s Savannah River Site - Paul G. Edwards; Karen F. Gaines; A. Lawrence Bryan; James M. Novak; Susan A. Blas (Environmental Monitoring and Assessment, 2014)

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

Cerebellar TMS in Treatment of a Patient with Cerebellar Ataxia: Evidence from Clinical, Biomechanics and Neurophysiological Assessments - Faranak Farzan; Yunfen Wu; Brad Manor; Elana M. Anastasio; Matthew Lough; Vera Novak; Patricia E. Greenstein; Alvaro Pascual-Leone (The Cerebellum, 2013)

Compositional and Thermal Evaluation of Lignocellulosic and Poultry Litter Chars via High and Low Temperature Pyrolysis - J. M. Novak; K. B. Cantrell; D. W. Watts (BioEnergy Research, 2013)

Effects of aging on apoptosis gene expression in oral mucosal tissues - Octavio A. Gonzalez; M. John Novak; Sreenatha Kirakodu; Arnold J. Stromberg; Shu Shen; Luis Orraca; Janis Gonzalez-Martinez; Jeffrey L. Ebersole (Apoptosis, 2013)

NM23 deficiency promotes metastasis in a UV radiation-induced mouse model of human melanoma - Stuart G. Jarrett; Marian Novak; Nathan Harris; Glenn Merlino; Andrezj Slominski; David M. Kaetzel (Clinical & Experimental Metastasis, 2013)

Photocatalytic degradation of gaseous toluene by using immobilized titania/silica on aluminum sheets - Minoo Tasbihi; Marko Kete; Ashok M. Raichur; Nataša Novak Tušar; Urška Lavrenčič Štangar (Environmental Science and Pollution Research, 2012)

Structure and mechanism of diet specialisation: testing models of individual variation in resource use with sea otters - M. Tim Tinker; Paulo R. Guimarães; Mark Novak; Flavia Maria Darcie Marquitti; James L. Bodkin; Michelle Staedler; Gena Bentall; James A. Estes (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 475–483 Abstract Studies of consumer‐resource interactions suggest that individual diet specialisation is empirically widespread and theoretically important to the organisation and dynamics of populations and communities. We used weighted networks to analyze the resource use by sea otters, testing three alternative models for how individual diet specialisation may arise. As expected, individual specialisation was absent when otter density was low, but increased at high‐otter density. A high‐density emergence of nested resource‐use networks was consistent with the model assuming individuals share preference ranks. However, a density‐dependent emergence of a non‐nested modular network for ‘core’ resources was more consistent with the ‘competitive refuge’ model. Individuals from different diet modules showed predictable variation in rank‐order prey preferences and handling times of core resources, further supporting the competitive refuge model. Our findings support a hierarchical organisation of diet specialisation and suggest individual use of core and marginal resources may be driven by different selective pressures.

Biochar’s role as an alternative N-fertilizer: ammonia capture - Kurt A. Spokas; Jeff M. Novak; Rodney T. Venterea (Plant and Soil, 2012)

Multiple mechanisms underlie metastasis suppressor function of NM23-H1 in melanoma - Marian Novak; Stuart G. Jarrett; Joseph R. McCorkle; Isabel Mellon; David M. Kaetzel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Vertical Distribution of Corn Stover Dry Mass Grown at Several US Locations - Wally W. Wilhelm; Jane M. F. Johnson; Dave T. Lightle; Douglas L. Karlen; Jeff M. Novak; Nancy W. Barbour; David A. Laird; John Baker; Tyson E. Ochsner; Ardell D. Halvorson; David W. Archer; Francisco Arriaga (BioEnergy Research, 2011)

Nutrient Removal as a Function of Corn Stover Cutting Height and Cob Harvest - Jane M. F. Johnson; Wally W. Wilhelm; Douglas L. Karlen; David W. Archer; Brian Wienhold; David T. Lightle; David Laird; John Baker; Tyson E. Ochsner; Jeff M. Novak; Ardell D. Halvorson; Francisco Arriaga; et al. (BioEnergy Research, 2010)

Evaluating the Illinois Stream Valley Segment Model as an Effective Management Tool - Stephen S. Warrner; Robert U. Fischer; Ann M. Holtrop; Leon C. Hinz; James M. Novak (Environmental Management, 2010)

Cytokinin Primes Plant Responses to Wounding and Reduces Insect Performance - Christopher Dervinis; Christopher J. Frost; Susan D. Lawrence; Nicole G. Novak; John M. Davis (Journal of Plant Growth Regulation, 2010)

Potential contributions of antimutator activity to the metastasis suppressor function of NM23-H1 - David M. Kaetzel; Joseph R. McCorkle; Marian Novak; Mengmeng Yang; Stuart G. Jarrett (Molecular and Cellular Biochemistry, 2009)

Benefits of Supplementation of an Electrolyte Scour Treatment with a Bacillus-Based Direct-Fed Microbial for Calves - C. A. Wehnes; K. N. Novak; V. Patskevich; D. R. Shields; J. A. Coalson; A. H. Smith; M. E. Davis; T. G. Rehberger (Probiotics and Antimicrobial Proteins, 2009)

Geospatial variability in the egg raft distribution and abundance of Culex pipiens and Culex restuans in Urbana‐Champaign, Illinois - B. G. Jacob; R. L. Lampman; M. P. Ward; E. J. Muturi; J. A. Morris; E. X. Caamano; R. J. Novak (International Journal of Remote Sensing, 2009)

Glacio-lacustrine stratigraphy, aquifer characterization and contaminant transport: a case study in South Lake Tahoe, California, USA - Craig W. Morgan; Graham M. Kent; Gordon G. Seitz; Michaela Novak (Hydrogeology Journal, 2008)

Clapper rails as indicators of mercury and PCB bioavailability in a Georgia saltmarsh system - J. C. Cumbee; K. F. Gaines; G. L. Mills; N. Garvin; W. L. Stephens; J. M. Novak; I. L. Brisbin (Ecotoxicology, 2008)

Physiological and molecular mechanisms of inorganic phosphate handling in the toad Bufo bufo - Nadja Møbjerg; Andreas Werner; Sofie M. Hansen; Ivana Novak (Pflügers Archiv - European Journal of Physiology, 2007)

Wound and insect herbivory responsive genes in poplar - Susan D. Lawrence; Christopher Dervinis; Nicole Novak; John M. Davis (Biotechnology Letters, 2006)

Arbuscular mycorrhiza alter the concentration of essential oils in oregano (Origanum sp., Lamiaceae) - T. Khaosaad; H. Vierheilig; M. Nell; K. Zitterl-Eglseer; J. Novak (Mycorrhiza, 2006)

The effect of varying levels of sodium bicarbonate on polychlorinated biphenyl dechlorination in Hudson River sediment cultures - Tao Yan; Timothy M. LaPara; Paige J. Novak (Environmental Microbiology, 2006)
Summary The addition of different concentrations of sodium bicarbonate had a profound effect on 2,3,4,5‐chlorobiphenyl (2,3,4,5‐CB) dechlorination in Hudson River sediment cultures. The most extensive dechlorination was observed in cultures to which 100 mg l −1 bicarbonate was added. Cultures amended with 1000 mg l −1 bicarbonate had the least extensive dechlorination, with 2,4‐CB and 2,5‐CB as predominant end‐products. A significant loss of total chlorinated biphenyl mass was observed in cultures to which ≤ 500 mg l −1 bicarbonate was added, suggesting that degradation beyond chlorinated biphenyls occurred. The dynamics of acetate formation were different among the treatments, with high acetate concentrations detected throughout the 303‐day experiment in cultures to which 1000 mg l −1 bicarbonate had been added. Sodium bicarbonate addition also had a significant impact on bacterial community structure as detected by polymerase chain reaction‐denaturant gradient gel electrophoresis (PCR‐DGGE) of 16S rRNA gene fragments. Three putative polychlorinated biphenyl (PCB) dechlorinators were identified; one Dehalococcoides ‐like population was detected in all enrichment cultures, whereas two Dehalobacter ‐like populations were only detected in the enrichment cultures with the most extensive dechlorination. These results suggest that the availability of bicarbonate, and potentially sodium, may affect PCB dechlorination in Hudson River sediment and thus need to be taken into consideration when assessing the fate of PCBs or implementing bioremediation.

Element Levels in Snakes in South Carolina: Differences Between a Control Site and Exposed Site on the Savannah River Site - J. Burger; S. Murray; K. F. Gaines; J. M. Novak; T. Punshon; C. Dixon; M. Gochfeld (Environmental Monitoring and Assessment, 2006)

Different patterns of the L-histidine decarboxylase (HDC) gene expression in mice resistant and susceptible to experimental cutaneous leishmaniasis - Z. Ps; K. Mller; I. Novak; E. Buzs; W. Solbach; A. Falus; T. Laskay (Inflammation Research, 2004)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Distribution of the cis-sabinene hydrate acetate-chemotype in accessions of marjoram (Origanum majorana L.) - Johannes Novak; Christina Bitsch; Friedrich Pank; Jan Langbehn; Chlodwig M. Franz (Euphytica, 2002)

Submaximal exercise in healthy volunteers: the relationship between gastric mucosal and systemic energy status - R. Rokyta; M. Matejovic; I. Novak; V. Zeman; A. Krouzecky; J. Novak; L. Trefil; K. Linhartova; V. Sramek (Pflügers Archiv - European Journal of Physiology, 2002)

Influence of Soil Aggregate Size on Atrazine and Trifluralin Leaching - S. M. Novak; J.-M. Portal; M. Schiavon (Bulletin of Environmental Contamination and Toxicology, 2001)

Multimedia Integrated Modeling for Environmental Protection: Introduction to a Collaborative Framework - John M. Johnston; Joan H. Novak; Stephen R. Kraemer (Environmental Monitoring and Assessment, 2000)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Different purinergic receptors lead to intracellular calcium increases in pancreatic ducts - B. C. Christoffersen; M. J. Hug; I. Novak (Pflügers Archiv - European Journal of Physiology, 1998)

Increased lovastatin formation by Aspergillus terreus using repeated fed-batch process - N. Novak; S. Gerdin; M. Berovic (Biotechnology Letters, 1997)

Replication of human cytomegalovirus in a rhabdomyosarcoma cell line depends on the state of differentiation of the cells - J. Cinatl; J. Cinatl; K. Radsak; H. Rabenau; B. Weber; M. Novak; R. Benda; B. Kornhuber; H. W. Doerr (Archives of Virology, 1994)

Long-term monitoring of polychlorinated biphenyls in the Hudson River (New York) using caddisfly larvae and other macroinvertebrates - M. A. Novak; A. A. Reilly; S. J. Jackling (Archives of Environmental Contamination and Toxicology, 1988)

Buchbesprechungen - B. M. Novak; Peter Perret (Aquatic Sciences, 1979)

Buchbesprechungen - Peter Perret; P. Bossard; B. M. Novak (Aquatic Sciences, 1974)